Dietary-Induced Signals That Activate the Gonadal Longevity Pathway during Development Regulate a Proteostasis Switch in Caenorhabditis elegans Adulthood - Shemesh, Netta; Meshnik, Lana; Shpigel, Nufar; Ben-Zvi, Anat (Frontiers in Molecular Neuroscience, 2017)
Cell-non-autonomous signals dictate the functional state of cellular quality control systems, remodeling the ability of cells to cope with stress and maintain protein homeostasis (proteostasis). One highly regulated cell-non-autonomous switch controls proteostatic capacity in Caenorhabditis elegans adulthood. Signals from the reproductive system down-regulate cyto-protective pathways, unless countered by signals reporting on germline proliferation disruption. Here, we utilized dihomo-γ-linolenic acid (DGLA) that depletes the C. elegans germline to ask when cell-non-autonomous signals from the reproductive system determine somatic proteostasis and whether such regulation is reversible. We found that diet supplementation of DGLA resulted in the maintenance of somatic proteostasis after the onset of reproduction. DGLA-dependent proteostasis remodeling was only effective if animals were exposed to DGLA during larval development. A short exposure of 16 h during the second to fourth larval stages was sufficient and required to maintain somatic proteostasis in adulthood but not to extend lifespan. The reproductive system was required for DGLA-dependent remodeling of proteostasis in adulthood, likely via DGLA-dependent disruption of germline stem cells. However, arachidonic acid (AA), a somatic regulator of this pathway that does not require the reproductive system, presented similar regulatory timing. Finally, we showed that DGLA- and AA-supplementation led to activation of the gonadal longevity pathway but presented differential regulatory timing. Proteostasis and stress response regulators, including hsf-1 and daf-16, were only activated if exposed to DGLA and AA during development, while other gonadal longevity factors did not show this regulatory timing. We propose that C. elegans determines its proteostatic fate during development and is committed to either reproduction, and thus present restricted proteostasis, or survival, and thus present robust proteostasis. Given the critical role of proteostatic networks in the onset and progression of many aging-related diseases, such a choice could impact susceptibility to protein misfolding diseases later in life.